Sistem Otomasi Pengendali pH Dan Oksigen Untuk Kolam Budidaya Ikan - Liberatus Liem; Ishak S. Limbong; Ben V Tarigan; Murni Pallawagau (Universitas Nusa Cendana, 2025)
In the development of fisheries, especially in tilapia cultivation, promising prospects have emerged with high market demand. However, fish farming still tends to use conventional methods that pay little attention to water quality. This deficiency can cause serious problems for fish health and quality, potentially detrimental to cultivation activities. To optimize fish growth, pH and dissolved oxygen control are necessary. This study created a microcontroller-based automation system to control pH (5-8.5) and dissolved oxygen (> 5 mg/L) in tilapia ponds. Field testing showed that the pH and dissolved oxygen sensors have low error rates of 5.07% and 4.80%, respectively. Laboratory testing showed that the system worked successfully with relative error percentage values of pH and DO testing of 5.71% and 20% of the setpoint.